Organizational Culture, Discipline, and the Politics of Self: Transformation Through Responsive Conversation. (April 2021) - McClellan, John G.
As organization and management scholars increasingly embrace organizations as social constructions, communication is more commonly recognized as the practice that creates, maintains, and changes organization. However, scholarship attending to organizational culture and identification often relies on unsophisticated perspectives of communication without much concern for power and the politics of language use. In this contribution, I review central ideas across four communicative perspectives for understanding and critiquing organization that complicate and reorient attention to organizational culture and identification. These perspectives direct attention toward meaning-making practices and social performances, the sociohistorical qualities of meaning and conflict suppression, tension-filled components of organization and the embodiment of meaning, and self-discipline and strategized self-subordination. Embracing the complexities offered in these communicative orientations, I invite scholars and practitioners to attend to responsive conversations about everyday experiences of organizational life to generate more mutually satisfying organizational cultures that celebrate diverse subjectivities at work.